Penyisihan Senyawa Organik pada Air Limbah Tahu Menggunakan Proses Elektrokoagulasi Pasangan Elektroda Aluminium - Ansiha Nur; Puti Sri Komala; Uttiya Annisa D (Dampak, 2020)
This study aims to determine the efficiency of organic removal in the form of Chemical Oxygen Demand (COD), Nitrate (NO3), and TSS of tofu wastewater with electrocoagulation process of aluminum electrode pairs with the monopolar arrangement. A two liters batch reactor and aluminum electrode (aluminum content of 95.7%) were used. Variations in current density (21 - 104 A / m2) and contact time (2 - 60 minutes). The optimum conditions were obtained at a current density of 104 A / m2 in 10, 15, and 2 minutes for COD, NO3, and TSS, respectively. The optimum removal efficiency for COD, NO3, and TSS were 95%, 69.64%, and 99.99%, respectively at a current density of 104 A/m2. Increases in current density and contact time were directly correlated with improvements in COD, NO3, and TSS removal effectiveness. The pH of wastewater has increased to 8.5. While the temperature of wastewater only increased in the 2nd minute to 27°C. Meanwhile, conductivity in wastewater decreases with increasing contact time. The decrease in conductivity is inversely proportional to the efficiency of pollutant reduction. The effluent of the results of this study has met the quality standards of Minister of Environment Regulation No. 5 of 2014 Attachment XVIII concerning Wastewater Quality Standards for Soybean Processing Businesses and/or Activities.Keywords: COD, electrocoagulation, aluminum electrodes, tofu wastewater, monopolar.ABSTRAKPenelitian ini bertujuan menentukan efisiensi penyisihan senyawa organik berupa Chemical Oxygen Demand (COD),Nitrat (NO3), dan Total Suspended Solid (TSS) air limbah pabrik tahu dengan proses elektrokoagulasi pasangan elektroda aluminium dengan susunan monopolar. Penelitian menggunakan reaktor batch dua liter dan elektroda aluminium (kandungan aluminium sebesar 95,7%). Variasi yang dilakukan adalah variasi rapat arus ( 21 - 104 A/m2) dan waktu kontak (2 – 60 menit). Kondisi optimum diperoleh pada kerapatan arus 104 A/m2 selama 10, 15, dan 2 menit untuk masing-masing COD, NO3, dan TSS. Efisiensi penyisihan optimum untuk COD, NO3 dan TSS masing-masing sebesar 95%, 69,64% dan 99,99 % pada rapat arus 104 A/m2. Peningkatan efisiensi penyisihan COD, NO3 dan TSS berbanding lurus dengan peningkatan rapat arus dan waktu kontak. pH air limbah mengalami peningkatan hingga 8,5. Temperatur air limbah hanya meningkat pada menit ke-2 menjadi 27°C. Sementara itu konduktivitas pada air limbah menurun seiring dengan bertambahnya waktu kontak. Penurunan konduktivitas berbanding terbalik dengan efiisiensi penyisihan polutan. Efluen hasil penelitian ini telah memenuhi baku mutu Peraturan Menteri Lingkungan Hidup No 5 Tahun 2014 Lampiran XVIII tentang Baku Mutu Air Limbah Bagi Usaha dan/ atau Kegiatan Pengolahan Kedelai.